Where russians should live: a counterfactual alternative to Soviet location policy - Tatjana Michajlova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper investigates the extent of distortions in Russia's spatial economy that are inherited from the Soviet system. Using Canada as a benchmark for spatial dynamics of economic activity in a market economy, I construct the spatial allocation of population that would result in Russia, given its initial conditions and existing regional endowments, in the absence of Soviet location policy. The results show that Siberia and the Far East were overpopulated by about 14.5 million people by the end of the Soviet period. Overdevelopment of Siberia comes at the expense of the European area of the country. This discrepancy persists, even after adjusting the simulated counter- factual allocation for WWII. – – , . , , , , . , 14,5 . . , .
Keywords: R1; P5; 330; location policy; Russia